Evaluasi Efektivitas Program Pengembangan Karir Guru dalam Meningkatkan Kompetensi Mengajar - Dhiyaulrizq, Ghina Azhzhahra; Kamaruddin, Syamsu A. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Teacher career development programmes are an important strategy for improving teaching competence and education quality. This study aims to evaluate the effectiveness of teacher career development programmes in improving teaching competence through a literature review of various relevant studies. Data were obtained from scientific articles discussing the impact of teacher training, Teacher Working Group (KKG) activities, Continuing Professional Development (CPD) policies, and various other teacher professional development strategies. The results of the study show that teacher career development programmes contribute positively to improving professional and pedagogical competence, teacher motivation, and the quality of the learning process in the classroom. However, a number of studies also reveal obstacles in their implementation, including suboptimal needs analysis, the incompatibility of training materials with learning practice needs, and limited continuous evaluation of the programme's impact. These findings emphasise that the success of teacher career development is largely determined by comprehensive programme planning, institutional support from schools, and the continuity of mentoring after training.